2017
DOI: 10.1007/s11701-017-0722-0
|View full text |Cite
|
Sign up to set email alerts
|

Tubeless outpatient robotic upper urinary tract reconstruction in the pediatric population: short-term assessment of safety

Abstract: Robotic upper urinary tract reconstruction (UUTR) has been widely utilized for surgical management of congenital obstruction. To further reduce morbidity and simplify postoperative care, outpatient robotic pyeloplasty (RP) and robotic ureteroureterostomy (RUU) were performed without ureteral stents, drains, or urethral catheters. The aim of the study was to assess the safety of performing tubeless robotic UUTR as an outpatient procedure. A retrospective review was performed for patients who underwent outpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
1
5
0
1
Order By: Relevance
“…15 More recently, Fichtenbaum et al showed a short series of 17 tubeless RALP in the outpatient setting. 11 In our study, a short-term assessment showed no complications, ER-visits, or readmissions 30 days after surgery. It is our belief that an experienced team and a well-established robotic program can safely perform an early discharge (≤24h) in the majority of patients.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…15 More recently, Fichtenbaum et al showed a short series of 17 tubeless RALP in the outpatient setting. 11 In our study, a short-term assessment showed no complications, ER-visits, or readmissions 30 days after surgery. It is our belief that an experienced team and a well-established robotic program can safely perform an early discharge (≤24h) in the majority of patients.…”
Section: Discussionsupporting
confidence: 50%
“…8,9 More recently, experienced surgeons are observing fast and uneventful recovery by patients undergoing robotic surgery and are pushing to discharge patients earlier or even doing robotic surgery as an outpatient procedure. 10,11 With that in mind, we sought to identify prognostic clinical features that would be associated with an early discharge (≤24h) after robotic pyeloplasty in children. This information would guide and reassure the pediatric urologist when deciding which subset of patients may be discharged with minimal risk.…”
Section: Discussionmentioning
confidence: 99%
“…Our early experience with tubeless robotic urinary tract reconstruction in 19 patients displayed excellent outcomes with all patients being discharged from the PACU without ureteral stents, drains or urethral catheters. 10 No 30-day complications, ER visits or readmissions were observed for any patient.…”
Section: Discussionmentioning
confidence: 89%
“…According to the available literature, there is not much difference in outcomes but a reduced cost with external stents [29,30]. While there are reports about tubeless robot-assisted pyeloplasties, stenting clearly seems to be the standard treatment [31].…”
Section: Acmentioning
confidence: 99%